Association of antiretroviral therapy with anal high-risk human papillomavirus, anal intraepithelial neoplasia, and anal cancer in people living with HIV: a systematic review and meta-analysis. Issue 4 (April 2020) - Kelly, Helen; Chikandiwa, Admire; Alemany Vilches, Laia; Palefsky, Joel M; de Sanjose, Silvia; Mayaud, Philippe
Summary: Background: The effect of antiretroviral therapy (ART) on the natural history of anal high-risk HPV and anal lesion progression is not well established. We reviewed the association of ART and other HIV-related factors on anal HPV infection, anal intraepithelial neoplasia (AIN), and anal cancer among people living with HIV. Methods: For this systematic review and meta-analysis, we searched MEDLINE and EMBASE for studies published between Jan 1, 1996, and Oct 30, 2019, that reported the association of HIV-related exposures (ART or highly active ART [HAART], HIV-RNA plasma viral load [PVL], and nadir or current CD4 cell count) with outcomes of anal high-risk HPV prevalence, incidence, and persistence; prevalence, incidence, progression, or regression of anal histological and cytological abnormalities; and anal cancer incidence. Effect estimates were extracted whenever available; otherwise, they were calculated from raw data. We assessed the risk of bias of included studies using the Newcastle-Ottawa scale, and random-effects meta-analyses were done to examine heterogeneity using the I 2 statistic. This study is registered on the PROSPERO database, CRD42018007271. Findings: We identified 6777 studies, of which 5377 were excluded before full-text review. 122 studies providing estimates for 130 distinct populations matched the inclusion criteria. The populations comprised 417 006 people living with HIV (women, men who have sex with men, and men who have sex with women). 41 (32%) population estimates were not stratified by sex or sexual orientation. People living with HIV receiving ART had 35% lower high-risk HPV prevalence than ART-naive people (crude odds ratio [OR] 0·65, 95% CI 0·54–0·79; I 2 12·1%, p=0·31) in 18 studies, and prolonged ART use was associated with a 10% reduction per year in high-risk HPV prevalence in two studies (adjusted OR 0·90, 0·85–0·95; I 2 0%, p=0·88). People living with HIV with undetectable PVL had lower HSIL-AIN2+ prevalence than those with detectable PVL (crude OR 0·84, 0·72–0·98; I 2 0%, p=0·80) in 16 studies, particularly if sustained for more than 1 year (crude OR 0·62, 0·47–0·81; I 2 0%, p=0·51). ART was not associated with anal cancer incidence when adjusted for years living with HIV in three studies (adjusted hazard ratio [HR] 1·11, 95% CI 0·68–1·80; I 2 0%, p=0·57), but ART users with sustained undetectable HIV PVL had 44% lower risk of anal cancer than those without (adjusted HR 0·56, 0·44–0·70; I 2 0%, p=0·94) and for each increase in nadir CD4 cell counts of 100 cells per μL, there was a 40% decrease in anal cancer incidence (crude HR 0·60, 0·46–0·78; I 2 21·7%, p=0·26). Interpretation: Effective ART use and early initiation at high nadir CD4 counts might reduce anal high-risk HPV infection and anal cancer risk. Although most studies were cross-sectional in design and few adjusted for potential confounders, this analysis provides comprehensive estimates of the effect of ART and HIV-related factors on the natural history of anal HPV-related disease in people living with HIV. Funding: EU Marie Skłodowska-Curie Actions programme.